KONSTITUSIONALITAS PEMBERHENTIAN HAKIM MAHKAMAH KONSTITUSI OLEH DEWAN PERWAKILAN RAKYAT - Ashari Ashari; Riska Ari Amalia (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this research is to find out the constitutionality of dismissal of judges of the Constitutional Court by the House of Representatives People. This research is a type of normative legal research that uses approach methods with legislation. The research results explain that The move of the House of Representatives towards the Constitutional Court is getting worse shows an attitude of authoritarianism and lawlessness, because the DPR violates the provisions of Article 24 paragraph (1) of the 1945 Constitution (1945 Constitution) which guarantee the existence of the independence of the judiciary power institution, the existence of regulations clear and firm regarding the possibility of dismissing a constitutional judge before the expiration of the term of office is intended to maintain independence and at the same time maintain the independence of judges, for this reason the dismissal of constitutional judges who do not referring to the rules of the Constitutional Court Law can be stated unconstitutional. Actions taken outside the provisions of the norms of Article 23 of the Constitutional Court Law is not in line with the 1945 Constitution because it has the potential to damage and disrupt judicial power as the main stronghold of the rule of law.